Pre-Service English Teachers’ Perceptions Towards The Use of Dialogical Learning as Reflective Practice: A Case Study - Santoso, Wulandari; Dito Mangkuluhur, Bahagia (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
In the context of English as a Foreign Language (EFL) teacher education, reflective practice is an integral part of the development of pedagogical practices, yet challenges persist in its effective implementation. This study investigates the perspectives of pre-service English teachers towards dialogical learning as part of reflective practice in a teaching practicum course in a private university in Jakarta. Employing semi-structured interviews with eight participants, the study reported the incorporation of reflective practice in the course, which was beneficial for improved teaching strategies, collaboration, and knowledge-sharing. However, the findings of this study revealed several challenges such as, demotivation to do reflective practice, lack of awareness of the importance of dialogical learning in reflective practice, and resource constraints. The study calls for the importance of explicit incorporation of dialogical learning as reflective practice in order to foster a culture of constructive feedback to enhance teacher development programs. In conclusion, this research contributes nuanced insights, urging a more intentional approach to reflective practices and dialogical learning in EFL teacher education for future pedagogical growth.